Performance evaluation of interrupted and hybrid channel heat sinks for a triple junction high concentrator photovoltaic cell - Muhammad Usman Sajid; Omer Abedrabboh; Yusuf Bicer (International Journal of Thermofluids)
High concentrator photovoltaic (HCPV) systems are designed to minimize the use of semiconductor materials by concentrating sunlight onto a smaller cell area. However, managing the excess heat generated during this concentration is a significant challenge, as it can affect the efficiency and lifespan of the HCPV cells. Effective thermal management solutions are essential to ensure reliable and cost-effective operation. The objective of this study is to propose interrupted and hybrid channel heat sinks designed to effectively maintain the temperature of HCPV systems within safe operating limits. The present work explores the impact of heat sink channel configuration, concentration ratio, and Reynolds number on the performance of a high concentration triple-junction solar cell. A comprehensive thermal model was developed in COMSOL Multiphysics, and numerical results were validated against multiple sets of available experimental and computational data, ensuring both accuracy and reliability. The results reveal that the hybrid channel design (Geometry F) significantly reduces the maximum solar cell temperature from 82 °C to 78 °C at CR = 1500 and Re = 400, achieving up to a 39.5 % increase in the Nusselt number compared to the conventional straight channel design (Geometry A). Additionally, Geometry (F) maintains a high performance evaluation criterion (PEC) value of 1.22 at Re = 200, reflecting effective thermal-hydraulic performance. Furthermore, Geometry (F) reduces the heat sink weight by 3.7 %, which is particularly advantageous for sun-tracking applications, where minimizing weight is essential.